Y-configured metallic stent combined with 125I seed strands cavity brachytherapy for a patient with type IV Klatskin tumor - Dechao, Jiao; Han, Xinwei; Yanli, Wang; Zhen, Li (Journal of Contemporary Brachytherapy, 2016)
We report a case in an inoperable patient with type IV Klatskin tumor treated by the use of a novel, two piece, Y-configured self-expandable metallic stent (SEMS) combined with two 125 I seed strands via bilateral approach. The placement of the Y-shaped SEMS was successful and resulted in adequate biliary drainage. After 2 months of intraluminal brachytherapy (ILBT), both 125 I seed strands and temporary drainage catheter were removed after patency of the expanded stents was confirmed by the cholangiogram. This technique was feasible and could be considered for the treatment of patients with Bismuth type IV Klatskin tumors.